Perception of a group of biology teachers from Argentina on the STS movement - Patrícia; Ana Patrícia; Ana Cristina (Uni-pluriversidad, 2014)
For a long time, the teaching of science conducted in the Science, Technology and Society (STS) perspective is being discussed and defended. Summarily, the STS approach can be understood as a movement that argues that science teaching should be concerned with “explaining the impact of science and technology in people’s lives” (Ferst, 2013). According to some researchers, since the sixties many curricula were developed in the light of the STS approach. In terms of teacher training, this perspective appears to be very relevant, since teachers are, in formal education, directly responsible for the formation of more critic and reflective decision making citizens. This article is the result of work done in Argentina with the purpose of analyzing the perceptions that teachers of Biological Sciences from different provinces had about the subject. It is a qualitative research that led us to conclude that teachers from Argentina have a satisfactory insight about STS, however it is evident that the initial offered training does not cover these discussions but they occur later in other courses.